2007
DOI: 10.17221/688-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Trans-free fats with the products of the oil palm - a selective review

Abstract: Berger K.G. (2007): Trans-free fats with the products of the oil palm -a selective review. Czech J. Food Sci., 25: 174-181.The results of nutritional research on fatty acids have led to the recommendation that the level of trans-fatty acids in foods (the products of partial hydrogenation of oils) should be reduced as far as possible. Palm oil and palm kernel oil are readily available and economical sources of solid fat. Formulae using oils to make fats for the main types of food products are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Physical properties of the fat are determined by the position of fatty acids in the TAG molecule, chemical composition, crystal structure, polymorph, SFC, hardness 5, 6 and by the processing conditions. Due to increased concern about the negative effects of trans‐fatty acids in the diet, there have been changes in food regulations 7, 8 and an increase in processes that avoid formation of trans fatty acids for the production of consumable fats. Processes such as fractionation, interesterification and blending are being increasingly used as alternatives to partial hydrogenation to minimise the trans‐fatty acid content of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties of the fat are determined by the position of fatty acids in the TAG molecule, chemical composition, crystal structure, polymorph, SFC, hardness 5, 6 and by the processing conditions. Due to increased concern about the negative effects of trans‐fatty acids in the diet, there have been changes in food regulations 7, 8 and an increase in processes that avoid formation of trans fatty acids for the production of consumable fats. Processes such as fractionation, interesterification and blending are being increasingly used as alternatives to partial hydrogenation to minimise the trans‐fatty acid content of foods.…”
Section: Introductionmentioning
confidence: 99%
“…A diet rich in specific fatty acids plays an important role in human physiology, e.g. unsaturated acids from the omega-3 group are highly significant in the prophylaxis of neoplastic diseases, cardiovascular disorders, and diseases of the immune system (Ezaki et al 1999;Ihara-Watanabe et al 2000;Kris-Etherton et al 2002;Berger 2007). Native antioxidants also protect the polyenic fatty acids against oxidation, thus improving the shelf-life of oils (Ruth at al.…”
mentioning
confidence: 99%
“…On the other hand, complete hydrogenation of a liquid vegetable oil will result in a fat of high melting point with zero trans fatty acids. In practice it can be used in food fats after interesterification with a soft oil (Berger 2007).…”
mentioning
confidence: 99%
“…In studies done by Smith et al [ 24 ], they showed that HRO provided a stable crystallization network structure when in seed butter matrix and this helped in maintaining a consistent hardness profile and thus prevented the oil migration. Concerning PKO, Berger [ 25 ] reported that it only contained 17% solid fat content at 25°C, and this characteristic may be a partial reason why it was ineffective as a stabilizer in the seed butter in our study. Compared with rapeseed oil, which has 49% erucic acid, this 22-carbon monounsaturated acid forms an effective crystalline structure after hydrogenation [ 26 ], and this probably helped the HRO in our study to provide a better support structure for homogeneity of the seed butter particles.…”
Section: Resultsmentioning
confidence: 60%